Pneumothorax after transbronchial needle biopsy - Boskovic, Tatjana; Stojanovic, Milos; Stanic, Jelena; Pena Karan, Slobodanka; Vujasinovic, Gordana; Dragisic, Dragan; Zarogoulidis, Konstantinos; Kougioumtzi, Ioanna; Dryllis, Georgios; Kioumis, Ioannis; Pitsiou, Georgia; Machairiotis, Nikolaos; et al. (Journal of Thoracic Disease; Vol 6, Supplement 4 (October 10, 2014): Journal of Thoracic Disease (Pneumothorax: From Definition to Diagnosis and Treatment), 2014)
Currently there several diagnostic techniques that re used by radiologists and pulmonary physicians for lung cancer diagnostics. In several cases pneumothorax (PNTX) is induced and immediate action is needed. Both radiologists and pulmonary physicians can insert a chest tube for symptom relief. However; only pulmonary physicians and thoracic surgeons can provide a permanent solution for the patient. The final solution would be for a patient to undergo surgery for a final solution. In our current work we will provide all those diagnostic cases where PNTX is induced and treatment from the point of view of expert radiologists and pulmonary physicians.